Resgatar a memória - Leite, Isabel Pereira (2013)
Without books, the World would be meaningless. It would be meaningless for we owe practically everything to those who came before us. And of those who came before, what has remained? Naturally, the record of their passage, the memory of their existence in multiple records. Anonymity does not exist because memory takes care of integrating the testimony of each individual in another concept – the collective. It is from the personal contribution that the collective lives – from the conjunction of nameless lives and of names that will be remembered for all times. It is in books, both in those that have disappeared and those we have preserved, that the Memory of the World lives on. Of the former, the latter bring us news. From these, we harvest each word so that they do not come to fall into oblivion. No one writes to be forgotten. They would not go to the trouble, if they did not think that what they want to transmit is important and should reach the future. It is for this very reason that readers are crucial. They are the ones who carry the memory and have the task of rescuing it at every moment. Memory, a quality of the human mind, a complex mechanism associated to several epithets, which in themselves are potential objects of analysis, is what books carry; what they have come to carry over the millennia, even if we cannot talk of the first «books» in these terms. Many are the supports on which the «written» record has been made. At the same time, perpetuity and destruction have coincided, at times promoting memory, at others, competing to destroy it. However, we continue to live among books; among books that talk of books, that talk of men of the past and the present; books which, already today, are books of the future.